Circulation levels of YKL-40 and Hs-CRP in stage 3 Molar-incisor pattern of periodontitis - Pinar Keles Yucel, Zeynep; Balli, Umut (Annals of Medical Research, 2021)
Aim: To evaluate the novel acute phase protein YKL-40 and high-sensitive C-reactive protein (Hs-CRP) in serum of patients with molar-incisor pattern of periodontitis (Stage 3, Grade C).Material and Methods: Twenty seven patients with molar-incisor pattern of periodontitis and 27 periodontally healthy individuals were included into the study. Serum levels of YKL-40 and Hs-CRP were measured by enzyme-linked immunosorbent assay.Results: Serum YKL-40 levels were significantly increased in molar-incisor pattern of periodontitis patients compared to healthy controls (P0.05). Similarly, significantly higher serum Hs-CRP levels were found in the patients with molar-incisor pattern of periodontitis than those of healthy ones (P0.05). There were positive correlations between serum YKL-40 and Hs-CRP and BOP in healthy control group (P0.05 for all). Moreover, serum YKL-40 showed positively strong relationships with Hs-CRP and also clinical periodontal parameters (CAL and BOP) in the periodontitis group (P0.001 for all).Conclusion: The present data suggest that YKL-40 might be a candidate biomarker for the diagnosis of localized to molar-incisor pattern of periodontitis and may also have the potential to predict the future risk of systemic diseases for this distinct form of periodontitis.
Keywords: Acute-phase proteins; C-reactive protein; human; periodontal diseases; serum; YKL 40 protein